2018
DOI: 10.1097/igc.0000000000001249
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-Assisted Infrarenal Para-aortic Lymphadenectomy in Gynecological Cancers: Technique and Surgical Outcomes

Abstract: Using the transperitoneal technique for PALND, the area between IMA and the renal veins can be reached in more than 80% of the operations, with a very low or 2.5% conversion rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…On the other hand, another study showed 47% positive pelvic nodes with positive paraaortic lymph nodes and 31% of patients with positive lymphovascular space invasion (LVSI) and metastasis to paraaortic lymph nodes. In patients with positive paraaortic lymph nodes and LVSI, 0.8% of cases were free of metastasis [6,28]. In our study, we did not have cases with metastases to paraaortic lymph nodes.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…On the other hand, another study showed 47% positive pelvic nodes with positive paraaortic lymph nodes and 31% of patients with positive lymphovascular space invasion (LVSI) and metastasis to paraaortic lymph nodes. In patients with positive paraaortic lymph nodes and LVSI, 0.8% of cases were free of metastasis [6,28]. In our study, we did not have cases with metastases to paraaortic lymph nodes.…”
Section: Discussioncontrasting
confidence: 44%
“…In 14 cases, the uterus was removed by mini laparotomy because of a narrow vagina or a large uterus. BMI of 35 kg/m 2 was the limit of successful lymphadenectomy; in cases with a BMI higher than 35, the complication rate was increased [28]. In our investigation, a few cases with BMI above 35 kg/m 2 were included.…”
Section: Discussionmentioning
confidence: 93%
“…A surgical advancement process called "minimally invasive surgery" has enabled minimizing the visibility of the infected area. The da Vinci Surgical System is a surgical robotics with a virtual 3D actuality visual acuity system that provides a greater profile in laparoscopic surgery where health professionals cannot physiologically see the affected area [ 24 ]. In 2000, the Food and Drug Administration approved the technology for clinical use [ 25 ].…”
Section: Reviewmentioning
confidence: 99%